Reduction Blood Pressureby Neck Massage Therapy Using Virgin Coconut Oil (VCO) and Dry Cupping Therapy - Nurul Faidah; Ni Kadek Muliawati (STIKes Patria Husada Blitar, 2021)
Hypertension is a non-communicable disease which increases every year, with the increasing incidence of Hypertension will have an impact on society, namely a decrease in health status which results in a decrease in the quality of life. Management of hypertension can be done with non-pharmacological therapy, one of the non-pharmacological therapies chosen by the community, namely complementary therapy, neck massage therapy using VCO and cupping is a complementary therapy that aims to reduce hypertension. The sampling technique used was purposive sampling. The sample in this study 16 respondents were given neck massage therapy with VCO and 16 respondents were given dry cupping therapy. The data analysis used was the Spearman rank because the data were not normally distributed. Before being given neck massage therapy with a mean VCO, systolic blood pressure was 156.25, diastolic blood pressure was 87.50 after being given a mean value of 124.38 and diastolic 81.25 with a systolic p value of 0.000 while for diastolic blood pressure of 0.008. Whereas in the group given dry cupping therapy systolic blood pressure with a mean of 158.82 and diastole a mean of 90.59, after being given dry cupping therapy, systolic blood pressure was 124.71 while diastole was 78.82 with a systolic p value of 0.000 and diastole of 0.009. The difference in blood pressure in the two interventions for the system p value was 0.968 while for diastole the p value was 0.625, which means there was no difference between the two interventions. So it can be concluded that both neck massage therapy with VCO and dry cupping therapy can reduce blood pressure in patients with hypertension.